Culturally Sensitive Care of Immigrant and Refugee Mothers with Babies in the NICU. Issue 1 (January 2022) - Callister, Lynn Clark
Abstract : Immigrant and refugee mothers with babies in the NICU face many challenges including barriers due to language, culture, unfamiliar hospital procedures, and lack of trust. Our global health and nursing expert, Dr. Callister, reviews recent studies on how to promote effective communication and culturally competent care of this vulnerable population.